Pengembangan Pemasaran Digital dan E-Commerce untuk Mendorong Pemberdayaan Ekonomi Produk Lokal Desa Lonuo - Nur Oktavin Idris; Jamal Darusalam Giu; Farid; Sri Nilawaty Lahay; Roys Pakaya (Unity Academy, 2024)
The limited access to marketing for local products in Lonuo Village and the use of less effective conventional methods to reach a broader market prompted the community service team to design a program aimed at empowering the local economy through the development of digital marketing and website-based e-commerce. The methods employed included awareness-raising, training, and the utilization of a website designed by the service team. This activity was attended by 17 participants, consisting of local business owners and members of the Lonuo Village community. The results of the activities revealed high enthusiasm among participants, who demonstrated the ability to understand digital marketing strategies. This program not only improved the community's understanding of digital marketing but also provided a platform to expand the market for local products. Furthermore, the program opened up opportunities for further development to ensure its sustainability.